Impact of Open access CT (OACT) for headache suspected of brain cancer in Lothian. (31st January 2018) - Zienius, Karolis; Grant, Robin; Brennan, Paul
Abstract: Guidance to General Practitioners on referral for direct-access brain imaging, based on levels of risks for CNS malignancy (red/orange/yellow) are proposed. However, the effect of such guidance upon referral behaviour is unknown. We reviewed all Open-Access-Computed- Tomography (OACT) referrals for possible CNS malignancy from Lothian-based GPs for 2010–2015. 3302 OACTs were performed. We report initial findings on a total of 54 scans positive for brain tumour (rate 1.63%). 57% were females, mean age 62 years. 57% patients had contrast-enhanced scan. There were 7 high-grade gliomas, 4 low-grade tumours, 16 metastases, 8 pituitary, 17 meningioma, 1 CNS lymphoma, and 1 skull metastasis. Six patients whose initial report queried a tumour had a normal follow-up imaging. All 6 patients had initial non-contrast scan only. Headache was the commonest complaint for patients whose scan identified a brain tumour: 16 referrals for headache-alone, 12 for headache-plus-neurological deficit, 4 for headache-plus-cognitive deficit and 22 for focal/cognitive symptoms but no headache. Time to scan from a referral, reported in median days, was: 19, 12.5, 18.5 and 17, respectively. It was shorter for patients with a known history of cancer (median, 9) than without (18) (MW u, p=0.06). Overall, pre-diagnostic symptomatic interval (median weeks) was longest for patients with non-focal symptoms: 14.4, 7.3, 14.8 and 9.6, respectively. Thirty-one (59.6%) referrals were for red-flag, 14 (26.9%) for orange-flag, and 7 (13.5%) for yellow-flag symptoms. We are now reviewing all OACTs and will report the frequencies of normal and significant abnormal other than brain tumour scans and will perform correlation whether these findings relate to a particular presenting symptom. We will report the frequency of symptom groups belonging to a suggested criteria of presumed risk of CNS malignancy (Kernick et al). We will also calculate measures of diagnostic performance for each symptom groups based on 3 levels of risk.